Applying Quantitative Approaches to the Formative Evaluation of Antismoking Campaign Messages. (December 2013) - Parvanta, Sarah; Gibson, Laura; Forquer, Heather; Shapiro-Luft, Dina; Dean, Lorraine; Freres, Derek; Lerman, Caryn; Mallya, Giridhar; Moldovan-Johnson, Mihaela; Tan, Andy; Cappella, Joseph; Hornik, Robert
This article shares an in-depth summary of a formative evaluation that used quantitative data to inform the development and selection of promotional ads for the antismoking communication component of a social marketing campaign. A foundational survey provided cross-sectional data to identify beliefs about quitting smoking, that campaign messages should target, as well as beliefs to avoid. Pretesting draft ads against quantitative indicators of message effectiveness further facilitated the selection and rejection of final campaign ads. Finally, we consider lessons learned from the process of balancing quantitative methods and judgment to make formative decisions about more and less promising persuasive messages for campaigns.